2013
DOI: 10.1586/ecp.13.17
|View full text |Cite
|
Sign up to set email alerts
|

Emerging artemisinin resistance in the border areas of Thailand

Abstract: Emergence of artemisinin resistance has been confirmed in Cambodia and the border areas of Thailand, the well-known hotspots of multidrug resistance Plasmodium falciparum. It appears to be spreading to the western border of Thailand along the Thai-Myanmar border, and will probably spread to other endemic areas of the world in the near future. This raises a serious concern on the long-term efficacy of artemisinin-based combination therapies, as these combination therapies currently constitute the last effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 138 publications
0
18
0
Order By: Relevance
“…Although sterile protection can be achieved by immunization with a low number of bites of malaria-infected mosquitoes under CQ coverage, widespread resistance to this drug limits the applicability of the CQ-ITV approach in malaria control. Artemisinin-based combination therapies are currently the treatment of choice for uncomplicated P. falciparum and P. vivax malaria in adults and children in all endemic areas (33), although there have been several reports of drug resistance in the same geographic area where CQ resistance originated in the 1950s, where artemisinin and its derivatives have been used as a monotherapy for more than three decades at subtherapeutic doses (34,35). Like CQ, AS prevents BS infection by blocking the ability of the parasite to complete the intraerythrocytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Although sterile protection can be achieved by immunization with a low number of bites of malaria-infected mosquitoes under CQ coverage, widespread resistance to this drug limits the applicability of the CQ-ITV approach in malaria control. Artemisinin-based combination therapies are currently the treatment of choice for uncomplicated P. falciparum and P. vivax malaria in adults and children in all endemic areas (33), although there have been several reports of drug resistance in the same geographic area where CQ resistance originated in the 1950s, where artemisinin and its derivatives have been used as a monotherapy for more than three decades at subtherapeutic doses (34,35). Like CQ, AS prevents BS infection by blocking the ability of the parasite to complete the intraerythrocytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Drug resistance to widely used artemisinin-based therapies (Carter et al, 2015;Hott et al, 2015) has become an imminent issue since drugresistance strains were identified in Bangladesh, Cambodia, Thailand, Vietnam, Myanmar and Laos (Haque et al, 2013;Na-Bangchang and Karbwang, 2013;Witkowski et al, 2013). Growing global efforts are focusing on finding new cures to combat malaria drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous emergence and spread of resistance to newly developed antimalarials (Cohen et al, 2010;Na-Bangchang and Karbwang, 2013;Price et al, 2014;WWARN, 2015) as well as vector resistance to insecticides (Dhiman and Veer, 2014;Strode et al, 2014) are key challenges against existing malaria control measures and highlights the urgent need for an effective vaccine. Despite several preclinical and clinical trials with the aim of developing an effective malaria vaccines (Moreno and Joyner, 2015), the most advanced malaria vaccine candidate in phase 3 trial, RTS,S/AS01, has only shown 31% and 50% efficacy in infants and children respectively (Foquet et al, 2014).…”
Section: Challenges Of Previous Intervention Strategiesmentioning
confidence: 99%